Differential Diagnosis in Internal Medicine From Symptom to Diagnosis - Walter Siegenthaler, MD (Stuttgart · New York, 2007)
The present book, Differential Diagnosis in Internal Medicine, first appeared as a German edition in 1952 and since then has been translated into 10 other languages. Over the past 50 years 19 German editions have been published, and now the 19th edition of the work, which has become the classic differential diagnosis textbook, is available in English for the first time. This book encompasses differential diagnosis across the spectrum of internal medicine, covering dermatology, neurology, and rheumatology, and provides the very latest knowledge including pathophysiological aspects. In contrast to encyclopedically structured textbooks, this book traces the path from symptom to diagnosis, just as the physician encounters the situation in the hospital and in the office. With this pragmatic approach—starting from the symptom(s)—the physician will usually succeed in substantiating the suspected diagnosis. Using this method, Siegenthaler’s Differential Diagnosis in Internal Medicine guides the reader through the differential diagnostic challenges in the entire field of internal medicine, including dermatology, neurology, and rheumatology. The book incorporates many relevant and instructive illustrations, tables, graphics, and algorithms, all contributing to the process of narrowing down a definitive diagnosis. The book is intended for medical students, physicians in clinical practice, generalists, and specialists in internal medicine, dermatology, neurology, and rheumatology, and also for all those concerned with the fundamental subjects of medicine, who wish to gain a competent knowledge of internal medicine. My thanks are due to all of the colleagues who worked with me on the book, and also to Thieme Publishing Group, in particular Thieme Publishers Stuttgart. I hope that, with the launch of the English edition, this classic textbook of differential diagnosis in internal medicine will now also find its place in the English-speaking world.